The Location of Iraq from the Map of the New World Economy (BRICS) Obstacles to Accession and its Effects (International Journal of Financial, Administrative and Economic Sciences, 2024)
The aim of the research was to clarify the location of Iraq from the map of the new world economy and the effects as well as the obstacles that will face Iraq in the event of its accession to the new world economy ( BRICS), where the research in its first research dealt with the conceptual framework related to the new world economy (BRICS) from concept to its strategic objectives, and then the challenges facing it, while the second research dealt with the topic of Iraq's location from its accession to the new world economy (BRICS) by addressing the economic effects of this accession as well as the obstacles that will face it before and after accession. The research has reached a set of results, including: There is no doubt that Iraq's accession to the new global economy (BRICS) will play an important role in the future of the Iraqi economy.
Keywords: Iraq; Location of Iraq; Map of the New World Economy; Effects; Obstacles to Accession